Acute mild traumatic brain injury is not associated with white matter change on diffusion tensor imaging. (11th May 2014) - Ilvesmäki, Tero; Luoto, Teemu M.; Hakulinen, Ullamari; Brander, Antti; Ryymin, Pertti; Eskola, Hannu; Iverson, Grant L.; Öhman, Juha
Abstract : Methodological limitations can confound DTI studies of traumatic brain injury. Using strict enrolment criteria to obtain an exceptionally homogeneous patient sample, Ilvesmäki et al . reveal that mild traumatic brain injury is not associated with DTI abnormalities detectable with tract-based spatial statistics. Changes in DTI measures are, however, seen with age. Abstract : This study was designed to (i) evaluate the influence of age on diffusion tensor imaging measures of white matter assessed using tract-based spatial statistics; (ii) determine if mild traumatic brain injury is associated with microstructural changes in white matter, in the acute phase following injury, in a large homogenous sample that was carefully screened for pre-injury medical, psychiatric, or neurological problems; and (iii) examine if injury severity is related to white matter changes. Participants were 75 patients with acute mild traumatic brain injury (age = 37.2 ± 12.0 years, 45 males and 30 females) and 40 controls (age = 40.6 ± 12.2 yrs, 20 males and 20 females). Age effects were analysed by comparing control subgroups aged 31–40, 41–50, and 51–60 years against a group of 18–30-year-old control subjects. Widespread statistically significant areas of abnormal diffusion tensor measures were observed in older groups. Patients and controls were compared using age and gender as covariates and in age- and gender-matched subgroups. Subgroups of patients with more severe injuries were compared to age-and gender-matched controls. No significant differences were detected in patient-control or severity analyses (all P -value > 0.01). In this large, carefully screened sample, acute mild traumatic brain injury was not associated with diffusion tensor imaging abnormalities detectable with tract-based spatial statistics.